Influence and effectiveness of horizontal diaphragms and cladding wall panels on the seismic behaviour of precast RC industrial buildings. (15th June 2023) - Ostetto, Liana; Sousa, Romain; Fernandes, Paulo; Rodrigues, Hugo
Highlights: The interaction of the roof's horizontal diaphragm with the structural and non-structural elements influences the seismic behaviour of industrial buildings. It was obtained a correlation between the stiffness required for a rigid behaviour at the roof level in terms of the shape of the building. The consideration of a rigid diaphragm tends to produce a more realistic seismic behaviour of the overall structure. The contribution of facade cladding wall panels significantly influences the seismic behaviour of the building, especially for high-rise buildings. Abstract: The seismic behaviour of precast reinforced concrete industrial structures has been extensively investigated in recent decades, especially after the damage caused by recent earthquakes. The interaction of the roof's horizontal diaphragm with the structural and non-structural elements can influence the seismic behaviour of these buildings. Thus, the present study aims to investigate this interaction, through nonlinear static and dynamic analyses using a simplified macro element to simulate the behaviour of cladding panels and an equivalent truss approach to simulate the roof in-plane stiffness. The analyses were performed on several structural models considering the current European single-storey precast reinforce concrete industrial building stock, with or without cladding wall panels, and with rigid or flexible diaphragm roof. Despite the uncertainties associated with the ability of common roof systems to ensure a rigid diaphragm, the analyses allowed the establishment of a correlation between the buildings generic properties and the roof horizontal stiffness required to approach a rigid diaphragm effect. In general, the results show that the consideration of a rigid diaphragm in numerical models may tend to produce a more realistic seismic behaviour of the overall structure. Furthermore, the contribution of facade cladding wall panels significantly influences the seismic behaviour of the building, especially for high-rise buildings.